Management of Noise Pollution - Suhanek, Mia (Environmental Sciences, 2023)
Noise pollution has a significant impact on our overall quality of life. This book aims to address different aspects of noise pollution and provide guidelines, noise policies, and laws regarding environmental noise and its challenges. The book draws attention to these policies and laws, which are often neglected and not implemented. One of the main issues today, especially for those living in urban areas, is traffic noise. The book discusses how such noise can be monitored and mitigated. Additionally, industrial noise poses a significant health risk for people working in noisy environments. The book emphasizes the need for special precautionary measures to preserve their health. The book also addresses infrasound noise exposure (≤ 20 Hz) and its negative impact on residential areas near wind power plants. Each chapter presents a specific type of noise pollution and proposes possible solutions and innovative approaches to dealing with the noise. Noise pollution management is a challenging task, and solutions must be creative since it is difficult to implement them once the problem already exists. This book aims to raise awareness about noise pollution, while presenting information and knowledge about current laws and guidelines. It offers innovative solutions to noise problems and specific case scenarios of noise pollution.